Penggunaan Media Sosial TikTok Sebagai Sarana Pembelajaran IPS dalam Meningkatkan Kreativitas Siswa di SMP Bina Umat (Jurnal Insan Pendidikan dan Sosial Humaniora, 2026)
The use of the social media platform TikTok as a learning medium in Social Studies (IPS) has emerged as an innovative strategy to enhance students’ learning creativity and engagement in the digital era and within the Merdeka Curriculum framework. This study aims to examine the effectiveness of TikTok in supporting creative learning processes, particularly in helping students understand Social Studies content in a visual, interactive, and easily accessible manner. The research was conducted through an online training seminar involving teachers and students, which included material delivery, demonstrations of TikTok usage, hands-on practice in creating learning content, and trial implementation in classroom learning activities. The analysis focused on three main aspects: (1) the improvement of teachers’ competencies in designing creative TikTok-based learning media, (2) students’ responses and learning experiences when using the platform, and (3) the effectiveness of the media in enhancing students’ understanding of Social Studies concepts. The results indicate that the use of TikTok improves the quality of learning media created by teachers and facilitates students’ independent learning. Pre-test and post-test data show an increase in students’ conceptual understanding, while student responses reveal a high level of learning interest through visual and interactive media. Nevertheless, several challenges related to device availability and internet connectivity were identified among some participants. In conclusion, TikTok is effective as an independent learning medium for Social Studies and contributes positively to improving students’ understanding and learning motivation. The study recommends continuous mentoring for teachers, strengthening ICT infrastructure, and further development of diverse learning media to support learning needs within the Merdeka Curriculum.